Research on the function failure of accelerometer servo circuit caused by hydrolysis and corrosion. (January 2022) - Wan, Huan huan; Xu, Xin; Zhang, Ming; Liu, Fa; Zheng, Dong fei; Ruan, Xiao ming
Highlights: The function failure phenomenon of the hybrid integrated quartz flexible accelerometer servo circuit caused by the corrosion and hydrolysis of the chip passivation layer is studied. The failure of integrated circuits caused by the hydrolysis of polyimide has been studied. The fault tree method is used to locate the failure of the quartz flexible accelerometer servo circuit. Analyze the failure phenomenon using micro analysis and characterization methods. Abstract: This paper studied the function failure of a quartz flexible accelerometer servo circuit manufactured by a thick-film hybrid integrated process. The circuit adopts the epoxy glue bonding process of the metal shell and the ceramic cover plate to encapsulate, and it is a non-airtight package. After the circuit is powered on, the quiescent current output is abnormal, and the DC voltage output is constant high potential, the acceleration detection function cannot be realized. In response to this phenomenon, the fault tree method is used to locate the failure location, and the fault is located at the abnormal function of the differential capacitor voltage converter chip. Using microscopic analysis and characterization methods, it can be seen that the hydrolysis and corrosion of the surface of differential capacitance-to-voltage converter chip causes leakage in the active area inside the chip, leads to the function failure of the circuit. The above research is of great significance to the design, storage and application of non-hermetic hybrid integrated circuits.